Report of 2009 International Workshop on Bioinformatics and Systems Biology in Traditional Chinese Medicine Research. (8th January 2010) - Xi, Dan; Chen, Su-Shing
The International Workshop on Bioinformatics and Systems Biology in Traditional Chinese Medicine (TCM) Research in conjunction with the 2009 International Joint Conferences on System Biology, Bioinformatics and Intelligent Computing (IJCBS2009), was held at Tongji University, Shanghai, China on August 3, 2009. This review discusses and summarises the scientific talks and achievements presented at the workshop and the impact of this workshop.